From Personal and Environmental Values to Green Beauty Loyalty: The Role of Satisfaction and Green Reward - I Made Surya Prayoga; Made Pradnyan Permana Usadi; I Komang Suryadnya Diputra (International Journal of Applied Business and International Management, 2026)
Growing environmental awareness among Generation Z has increased demand for sustainable consumption, particularly in the cosmetics industry. However, the mechanisms through which value orientation influences green beauty loyalty remain unclear. This study examines the effects of altruistic and egoistic values on green beauty loyalty, with green satisfaction as a mediating variable and green reward as both a direct predictor and moderating factor. A quantitative approach was employed using data collected from 280 Indonesian Generation Z consumers who have prior experience with green cosmetic products. The data were measured using a seven-point Likert scale and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that egoistic value (? = 0.424, p = 0.006) and altruistic value (? = 0.443, p = 0.003) significantly enhance green satisfaction, which strongly influences green beauty loyalty (? = 0.788, p 0.001), indicating full mediation. However, the direct effects of both values on loyalty are not significant. Green reward exerts a significant direct effect on loyalty (? = 0.402, p 0.001) but does not moderate the satisfaction–loyalty relationship (p = 0.980). These results highlight the pivotal role of satisfaction and suggest that reward mechanisms function as independent drivers of sustainable consumer loyalty, offering both theoretical and managerial implications.